2021
DOI: 10.1097/ju.0000000000001408
|View full text |Cite
|
Sign up to set email alerts
|

Urotrauma Guideline 2020: AUA Guideline

Abstract: The authors of this guideline reviewed the urologic trauma literature to guide clinicians in the appropriate methods of evaluation and management of genitourinary injuries. Materials and Methods: The Panel amended the Guideline in 2020 to reflect additional literature published through February 2020. When sufficient evidence existed, the Panel assigned the body of evidence a strength rating of A (high), B (moderate), or C (low) for support of Strong, Moderate, or Conditional Recommendations. In the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 26 publications
1
81
1
1
Order By: Relevance
“…Based on the ASST classification, renal gunshot injury results in a grade IV injury. Abdominal exploration was reserved only if there were hemodynamic instability, renal hilar involvement, and active haemorrhage (11) . Gunshot injuries to the kidney are commonly associated with thoracic and abdominal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the ASST classification, renal gunshot injury results in a grade IV injury. Abdominal exploration was reserved only if there were hemodynamic instability, renal hilar involvement, and active haemorrhage (11) . Gunshot injuries to the kidney are commonly associated with thoracic and abdominal injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamically unstable patients and patients with other hollow viscus injuries are not candidates for MIM [ 6 ]. For extraperitoneal injury, operative repair is recommended if the patient is already undergoing pelvic surgery for another injury such as exploratory laparotomy or orthopedic repair of the pelvis [ 2 , 3 ]. Complicated injuries involving the ureteral orifice or trigone may require surgery to prevent future incontinence [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the 2004 Eastern Association trauma guidelines for genitourinary trauma for all mechanisms, Holevar reported that catheter drainage shows results equal to surgical repair [ 6 ]. The latest AUA guidelines recommend MIM with drainage for extraperitoneal bladder injury without mention of injury mechanism [ 3 ]. Bryk published a 2013 review of urologic trauma guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up CT imaging 48–72 hours after initial imaging is recommended in patients with high-grade renal injury (American Association for the Surgery of Trauma [AAST] grades IV-V), given the increased risk for complications such as hemorrhage, urinoma, and fistula formation. 1 We present the case of a patient with an AAST grade IV renal injury who demonstrated vicarious excretion of intravenous contrast into the bowel masquerading as a nephroenteric fistula.…”
Section: Introductionmentioning
confidence: 99%